Image Compression based on Adaptive Polynomial Coding of Hard & Soft Thresholding - Al-Khafaji , Ghadah; Mahdi , Noor Sabah (Iraqi Journal of Science, 2022)
In this paper, an adaptive polynomial compression technique is introduced of hard and soft thresholding of transformed residual image that efficiently exploited both the spatial and frequency domains, where the technique starts by applying the polynomial coding in the spatial domain and then followed by the frequency domain of discrete wavelet transform (DWT) that utilized to decompose the residual image of hard and soft thresholding base. The results showed the improvement of adaptive techniques compared to the traditional polynomial coding technique.